Factors of contraban cigarettes smuggling in Malaysia - Vijayan, Kamalashan; Mariamdaran Chethiyar, Saralah Devi; Muniandy, Venothiney Dewi (Universitas Islam Malang, 2022)
The Royal Malaysian Customs Department takes seriously the issue related to cigarette smuggling activities which due to the study conducted put the smuggled cigarette market and the sale of smuggled cigarettes in this country is the largest in the world. This study aims to examine the issues related to cigarette smuggling in Malaysia. The research methodology is to use the library research method. The findings of the study are based on previous studies. This study focuses on the factors of smuggling in Malaysia. The results of the study can list the main factors that contribute to the widespread smuggling of cigarettes in Malaysia. The findings of this study on the factor of cigarette smuggling can be used as a guide to further improve control and enforcement at the country's entrances. The implementation of research rpelated to the type and form of punishment that can be imposed on those convicted of smuggling prohibited goods, especially contraband cigarettes. The second is the formation of a police community consisting of the general public.